2002
DOI: 10.1021/ja012700p
|View full text |Cite
|
Sign up to set email alerts
|

From Sulfoxide Precursors to Model Oligomers of Conducting Polymers

Abstract: The gas-phase internal elimination (E(i)) reaction of the sulfoxide (-SO-CH(3)) precursors of ethylene and model oligomers of PPV and PITN has been investigated by means of Hartree-Fock, Møller-Plesset (second and fourth order), and Density Functional Theory (B3LYP, MPW1K) calculations. Considerable differences between the obtained ground state and transition state geometries and the calculated activation energies are observed from one approach to the other, justifying first a careful calibration against the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 69 publications
5
23
0
Order By: Relevance
“…The MP2/6‐31G* and to a lesser extent the MPW1K/6‐31G* results better match the CCD/6‐31G* structural data than those obtained at the B3LYP/6‐31G* level. This confirms the superiority of the MPW1K functional over the B3LYP one in describing highly stretched configurations such as transition states,10, 17, 18 for which electronic exchange is significantly more important than for ground‐state equilibrium configurations.…”
Section: Assessment Of the Theoretical Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The MP2/6‐31G* and to a lesser extent the MPW1K/6‐31G* results better match the CCD/6‐31G* structural data than those obtained at the B3LYP/6‐31G* level. This confirms the superiority of the MPW1K functional over the B3LYP one in describing highly stretched configurations such as transition states,10, 17, 18 for which electronic exchange is significantly more important than for ground‐state equilibrium configurations.…”
Section: Assessment Of the Theoretical Methodssupporting
confidence: 59%
“…In straightforward anology with previous investigations of the E i conversion of sulfoxide10 and sulfonyl11 precursors, the first goal of this article is to assess the relative performance of approaches such as the Hartree–Fock (HF)12 and second‐, third‐, and partial fourth‐order Møller–Plesset [MP2,13 MP3, MP4(SDQ)] theories, as well as density functional theory (DFT),14 for describing the E i reactions of xanthate precursors, using basis sets of increasing size. In this article, we will specifically compare the B3LYP15, 16 and MPW1K17, 18 functionals (namely, Becke three‐parameter Lee–Yang–Parr and modified Perdew–Wang one‐parameter model for kinetics).…”
Section: Introductionmentioning
confidence: 86%
“…The other selected functional is the so‐called MP1WK,49 which has been optimized to a database of barrier heights and reaction energies. Several studies have demonstrated that MP1WK model gives remarkably good performance for kinetics 51, 56–59. However, the increased percentage of Hartree‐Fock exchange in MPW1K deteriorates the atomization energy calculation 49.…”
Section: Computational Frameworkmentioning
confidence: 99%
“…In a previous contribution,35 the gas‐phase internal elimination ( E i ) reaction of the sulfoxide (SOCH 3 ) precursor of ethylene has been investigated by means of Hartree–Fock,36 and Møller–Plesset36, 37 (second and fourth order) theories, as well as with Density Functional Theory38 using the hybrid and gradient corrected B3LYP39 (Becke‐3‐parameters Lee–Yang–Parr) and MPW1K40 (Modified Perdew–Wang one‐parameter model for kinetics) functionals. In this study, the efficiency of these approaches in describing E i reactions has been carefully assessed by comparison with available experimental data and theoretical results obtained at the CCSD(T)41 level and using basis sets as large as the Dunning's correlation consistent polarized valence basis sets of double, triple, and quadruple ζ quality, designated as cc‐pVXZ, with X = D,T,Q, respectively 42.…”
Section: Introductionmentioning
confidence: 91%